Plasmakoncentration av hjärtspecifikt troponin I under konvertering med kinidinsulfat hos hästar med förmaksflimmer - Brodd, Stephanie (2019)
Atrial fibrillation is the most common performance-limiting arrhythmia in horses. In Sweden, atrial fibrillation is treated medically with quinidine sulphate. The aim of this pilot study was primarily to investigate if medical conversion with quinidine sulphate could cause damage to myocytes identified as an increase of cardiac specific troponin I (cTnI) in plasma. In addition, this study also investigated whether an association could be seen between concentrations of cTnI in plasma and the outcome of the treatment. Furthermore, this study also investigated the side effects of quinidine sulphate as well as electrocardiographic changes during treatment.